KENOTIC DIALOGUE – A PARADIGM FOR CHRISTIANS’ RELATIONS WITH THEIR NEIGHBORS - STANCIU, Teofil (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2022)
This article represents an attempt to argue that if we are to apply Christ’s kenosis to our relationships, then a kenotic dialogue will be the appropriate way to interact with others. Starting from Martin Buber and some Christian thinkers, this paper will also emphasize the relational dimension of God’s image in human beings and the subsequent dialogue this image entails. Assuming the premise that Jesus Christ is the perfect human expression of God’s image and that this reality also impacts our human nature, the consequence might be that his kenotic dialogue with the world prompts an analog dialogue between God and us (in prayers) and between our neighbors and us. Because kenosis can be a tricky concept, it is adequate to mention that the kenotic perspective employed in this paper is that set out by the Orthodox theologian Dumitru Stăniloae. Finally, we hope to convince the reader that Christ’s kenosis is simultaneously the foundation and the model for our relationships network and enables us to a new way of interacting with people.